Design and Website Design for Vivree Photography - Eliezer, Jonathan Jami'an (VCD: Journal of Visual Communication Design, 2023)
Vivree Photography is a wedding photography service domiciled in Surabaya with a target market of millennials aged 22 - 30 years. Vivree Photography has been established since 2019 and has been running a photography business that focuses on wedding photography and has met many consumers. After evaluating this professional impression, the website is felt to be very important because it is an image and also to be trusted in the field of business that is involved by looking at other competitors. The website as a professional image also enables competitors to create marketing to increase customer engagement. This research uses a literature study in the form of a literature review using national and international journals and books that discuss websites for business, UI / UX on websites and customer engagement. In addition, the literature review method is also carried out using quantitative methods with expert users who are competent in technology and photography, extreme users who have used the services of Vivree Photography, and a discussion group forum by 15 people aged 22-30 years to review the results of websites that have been published. create and provide further suggestions for the Vivree Photograph website. Therefore, from the results of the research, it can be concluded that website design and UI / UX design which has a monochrome minimalist design style and has a warm tone and emphasis on writing and features on the website are very important for a business website, especially a service business in order to improve marketing and also customers. engagement Vivree Photography. Keywords: Professional, Design, Website, Promotional Media, Consumer